Case of a 10-month-old male feline with focal tracheal stenosis due to tracheal rings agenesia associated with fibro-necrotic tracheitis (Veterinary Science, 2023)
Although congenital tracheal anomalies are not very common in veterinary medicine, they are still very important. Just as happens in human medicine, most possible variants are of very striking clinical presentation, due to the respiratory distress produced in patients. All require some type of surgical or minimally invasive correction in order to overcome the acute condition. Below is the case of a 10-month-old male feline that attended the emergency ward with acute inspiratory and expiratory dyspnea, who particularly presented marked inspiratory stridor. As a result of the patient’s decease and subsequent necropsy and histopathology it was concluded that he presented segmental congenital tracheal stenosis due to absence of tracheal rings.
Keywords: Dyspnea; stridor; Felines; Tracheal stenosis; Congenital; Emergency